2017
DOI: 10.5194/bg-14-5069-2017
|View full text |Cite
|
Sign up to set email alerts
|

Seagrass as major source of transparent exopolymer particles in the oligotrophic Mediterranean coast

Abstract: Abstract. The role of seagrass, Posidonia oceanica, meadows as a source of transparent exopolymer particles (TEPs) to Mediterranean coastal waters was tested by comparing the TEP dynamics in two adjacent coastal waters in the oligotrophic NW Mediterranean Sea, one characterized by oligotrophic open-sea waters and the other accumulating seagrass leaf litter, together with an experimental examination of TEP release by seagrass litter. TEP concentrations ranged from 4.6 to 90.6 µg XG (xanthan gum) Eq L −1 , wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
17
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 33 publications
4
17
2
Order By: Relevance
“…The TEP concentrations that we measured across the OAO (CU included) generally fall within the range reported in other studies from the open ocean (Table 2). However, our levels are higher than those observed in the Mediterranean Sea , Pacific Ocean (Ramaiah et al, 2005;Kodama et al, 2014;Iuculano et al, 2017b) and one study in the northwestern Atlantic Ocean (Cisternas-Novoa et al, 2015), and lower than that reported in the eastern Mediterranean Sea (Bar-Zeev et al, 2011). We believe that one of the reasons for the higher values found in our study compared with these previous studies is the depth.…”
Section: Teps Across the Surface Atlantic Oceancontrasting
confidence: 87%
See 4 more Smart Citations
“…The TEP concentrations that we measured across the OAO (CU included) generally fall within the range reported in other studies from the open ocean (Table 2). However, our levels are higher than those observed in the Mediterranean Sea , Pacific Ocean (Ramaiah et al, 2005;Kodama et al, 2014;Iuculano et al, 2017b) and one study in the northwestern Atlantic Ocean (Cisternas-Novoa et al, 2015), and lower than that reported in the eastern Mediterranean Sea (Bar-Zeev et al, 2011). We believe that one of the reasons for the higher values found in our study compared with these previous studies is the depth.…”
Section: Teps Across the Surface Atlantic Oceancontrasting
confidence: 87%
“…Chl a concentration in the OAO (0.4 ± 0.2 mg m −3 (0.2-0.6 mg m −3 )) was generally higher than in the other studies referred in the Table 2. For example, in Iuculano et al (2017b) Chl a ranged 0.05-0.31 mg m −3 , and in Kodama et al (2014) it averaged 0.05 ± 0.01 mg m −3 . We also cannot discard the possibility that differences in TEP chemical composition could cause differences in staining capacity.…”
Section: Teps Across the Surface Atlantic Oceanmentioning
confidence: 96%
See 3 more Smart Citations